STUDI PERBANDINGAN TENTANG NILAI-NILAI KERJA BERDASARKAN PENDIDIKAN ORANG TUA DAN ASPIRASI KERJA SLTA NEGERI DI KODYA SURAKARTA - Daliman, Daliman (Indigenous, 1995)
The aim of this research is to know the differences of work values based on the differences of parentss levels of education, work aspirations, kind of school or school departement, and sex.The method employed to et the samples was "cluster purposive random sampling". The number of students taken as the samples was 582 coming from various departements of different senior high-school; the departements of social and natural sciences, and the teacher training in Surakarta. The instrumen employed to evoke work values scale 1989. to know the parents levels of education, work aspirations, kinds of school or school departement and sex a set of a questionnaire was used. Data analysis was conducted by means of "one-way-simulataneous analysis of variance". A post hoc analysis was also conducted by means of the test.          The research results were as follows:There were no differences of work-values either of economic, non-economic, achievement or influence based on the differences of the parents levels of education.The students whose parents level of education was higher than junior high-school gave more attention to the affiliation and common work-values than those whose parents level of education was junior high-school or lower.There were no differences of work-values either of economic, non-economic, achievement of affiliation based on differences of the studentss work aspirations.The students whose work aspirations wa s to goverment emloyees gave more attention to the influence and common work values than those whose work aspiration was to become private employees or entrepreneurs.There were no differences ot economic work-value between the students, of social and natural sciences departements, the students of economic, engineering, and family prosperty school, on one hand, and those or teacher training school on one hand, and those of teacher training son the other hand.The students of teacher training school gave more attention to the non-economic, influence and common work-values than those of social and natural sciences departements, and of economic, engineering, family prosperity schools.The students of natural sciences depatement gave more attention to the achievement work-value than those of the other departements of school.The students of family prosperity and the economic schools tend to pay more attention to the affiliation work-values than those of the other departements or schools.There were no differences of achievement and economic work-values between male and female students of senior high-school.Female students gave more attention to the nn economic, affiliation, influence and common work-valuthmale students.